Trends in transfusion‐transmissible infections among Australian blood donors from 2005 to 2010. Issue 11 (5th March 2013) - Lucky, Tarana T.A.; Seed, Clive R.; Keller, Anthony; Lee, June; McDonald, Ann; Ismay, Susan; Wand, Handan; Wilson, David P.
<x xml:space="preserve">Abstract</x> Background Routine monitoring of trends in transfusion‐transmissible infections (TTIs) is essential to maintaining and improving transfusion safety. Although periodic studies have been published there is no comprehensive trend analysis for TTIs in Australian donors. This study determined recent trends in TTIs for which testing is conducted in Australia and described key attributes of infected blood donors. Study Design and Methods This is a retrospective analysis using data on donation testing for TTIs (2005‐2010) from the national blood service donor database and data on postdonation interviews with TTI‐positive donors (2008‐2010) from a risk factor database incorporating responses to standardized interview questions. The study measured the prevalence and incidence of TTIs in Australia and assessed their time trends. Multivariate analysis of time trends was conducted using Poisson regression models. Results Overall, the prevalence and incidence of TTIs in 2005 to 2010 remained low and steady. The prevalence of hepatitis C virus decreased (rate ratio [RR], 0.93; 95% confidence interval [CI], 0.89‐0.97) and the prevalence of active syphilis increased (RR, 1.51; 95% CI, 1.15‐1.99) significantly during the study period. Prevalence of TTIs among Australian blood donors was substantially lower than that in the general population and no unique risk factors were identified in test‐positive blood donors when compared with the general population. Conclusion Both the prevalence and the incidence of TTIs in Australian blood donors remained low, with a steady or declining trend for most infections except active syphilis. The lower prevalence of TTIs in blood donors compared with the general population reflects the effectiveness of donor education and donor selection measures in Australia.